Sago Caterpillar (Rhynchophorus ferrugineus) Flour Improve Insulin-Like Growth Factor 1 (IGF-1) Levels in Low-Protein Diet Rats - Lara Ayu Lestari; William Ben Gunawan (Universitas Aisyah Pringsewu, 2022)
Lack of protein-energy (KEP) is a condition of malnutrition that is specific to the inadequate intake of energy and protein for the growth and maintenance of the body. Sago caterpillar flour (Rhynchophorus ferrugineus) contains the essential amino acids phenylalanine and lysine which affect IGF-1 levels. The purpose of the study was to analyze the effect of sago caterpillar flour (Rhynchophorus ferrugineus) on IGF-1 levels in a low-protein diet of Wistar rats. This study utilizes true experimental pre and post-group control design. The male Wistar rats (n=28 mice; body weight 100-150 g) were randomly divided into 4 groups (n=7), consisting of group K (-) which was given a standard diet of AIN-93 as a control; Group K (+) which was given a diet of AIN-93 modifications of a low-protein diet; the P1 group which was given AIN-93 modified diets low in protein and sago caterpillar flour of 0.36g/100 g BW/day; and the P2 group which was given AIN-93 modified diets low in protein and sago caterpillar flour of 1.36g/100 g BW/dayfor 28 days. IGF-1 levels were measured using the ELISA method. Statistical analysis using paired t-test and one-way ANOVA test. There was a significant increase in IGF-1 levels before and after the intervention in the treatment group (p=0.000). There was a significant difference in IGF-1 levels in the P1 and P2 groups compared to the K+ group (p=0.000). There was a significant difference in IGF-1 levels between P1 and P2 (p=0.000). Sago caterpillar flour of 0.36 g/100 g BW/day may increase IGF-1 levels in rats with a low-protein diet.Abstrack: Kekurangan energi protein (KEP) merupakan kondisi gizi kurang yang spesifik akibat kekurangan asupan energi dan protein untuk pertumbuhan dan pemeliharaan tubuh. Tepung ulat sagu (Rhynchophorus ferrugineus) mengandung asam amino esensial fenilalanin dan lisin yang mempengaruhi kadar IGF-1. Tujuan penelitian untuk menganalisis pengaruh pemberian tepung ulat sagu (Rhynchophorus ferrugineus) terhadap kadar IGF-1 pada tikus Wistar diet rendah protein. Penelitian menggunakan desain true experimental yang terdiri atas kelompok kontrol dengan perlakuan pre dan post intervensi. Tikus yang digunakan adalah tikusWistar jantan (n=28 tikus; berat badan 100-150 g) yang secara acak dibagi menjadi 4 kelompok (n=7), yaitu kelompok K (-) yang diberi diet standar AIN-93 sebagai kontrol; kelompok K (+) yang diberi AIN-93 dengan modifikasi diet rendah protein; kelompok P1 diberi AIN-93 modifikasi diet rendah protein dan tepung ulat sagu 0,36g/100 g BB/hari; kelompok P2 diberi AIN-93 modifikasi diet rendah protein dan tepung ulat sagu 1,36g/100 g BB/hari, dengan perlakuan selama 28 hari. Kadar IGF-1 diukur menggunakan metode ELISA. Analisis statistik menggunakan uji paired t-test dan one way ANOVA.Ada peningkatan signifikan kadar IGF-1 sebelum dan sesudah intervensi pada kelompok perlakuan (p=0,000). Ada perbedaan yang signifikan kadar IGF-1 pada kelompok P1 dan P2 dibandingkan kelompok K+ (p=0,000). Ada perbedaan yang signifikan kadar IGF-1 yang signifikan antara P1 dibandingkan P2 (p=0,000). Tepung ulat sagu 0,36 g/100 g BB/hari dapat meningkatkan kadar IGF-1 pada tikus dengan diet rendah protein.